MENJAWAB KENDALA PEMBUKTIAN DALAM PENERAPAN ALAT BUKTI ELEKTRONIK - Dewi Asimah (Puslitbang Hukum dan Peradilan bekerja sama dengan Ditjen Badimiltun, 2020)
The existence of electronic information and / or electronic documents has been recognized as valid evidence which is an extension of the evidence in the Procedure Law that applies in Indonesia provided that the electronic information and / or electronic documents use electronic systems in accordance with the provisions stipulated in Law No. 19 of 2016 concerning Amendments to Law No. 11 of 2008 concerning Electronic Information and Transactions. However, despite the ITE Law as well as several other regulations, it cannot be said that the Indonesian Procedural Law has stipulated electronic evidence in evidence, because the regulation of electronic evidence is in the realm of material law. Proof using electronic evidence at the trial has debates such as the examination of witnesses using the teleconference in the case of BULOG and marriage /consent qobul conducted different countries. Besides there are several other obstacles such as 1. Authentication of electronic evidence 2. Procedures for showing the instrument electronic evidence and 3. Electronic signatures. Responding to these constraints, the renewal of the procedural law must be carried out immediately by including the electronic evidence and changing the evidence system from a closed proof system to an open proof system, in order to accommodate the development of evidence, especially electronic evidence.